What Predicts Method Effects in Child Behavior Ratings. (April 2015) - Low, Justin A.; Keith, Timothy Z.; Jensen, Megan
The purpose of this research was to determine whether child, parent, and teacher characteristics such as sex, socioeconomic status (SES), parental depressive symptoms, the number of years of teaching experience, number of children in the classroom, and teachers' disciplinary self-efficacy predict deviations from maternal ratings in a multitrait-multimethod (MTMM) confirmatory factor analysis. The study included 978 families from the National Institute of Child Health and Development Study of Early Child Care and Youth Development. Results indicated that teachers with more disciplinary self-efficacy, teaching experience, and children in their classrooms generally rated their students' behavior in a more consistent manner with ratings completed by the students' mothers. In addition, fathers who reported more symptoms of depression rated their children's behavior in a less consistent manner with ratings completed by mothers. Finally, the perspectives of mothers generally deviated more from the perspectives of fathers and teachers when they were rating boys.